CTS1: a p53-derived chimeric tumor suppressor gene with enhanced in vitro apoptotic properties. - Conseiller, E; Debussche, L; Landais, D; Venot, C; Maratrat, M; Sierra, V; Tocque, B; Bracco, L (The Journal of Clinical Investigation, 1998)
The clinical potential of the p53 tumor suppressor gene is being evaluated currently for gene therapy of cancer. We have built a variant of wild-type p53, chimeric tumor suppressor 1 (CTS1), in which we have replaced the domains that mediate its inactivation. CTS1 presents some very interesting properties: (a) enhanced transcriptional activity; (b) resistance to the inactivation by oncogenic forms of p53; (c) resistance to the inactivation by MDM2; (d) lower sensitivity to E6-induced degradation; (e) ability to suppress cell growth; and (f ) faster induction of apoptosis. Thus, CTS1 is an improved tumor suppressor and an alternative for the treatment of wild-type p53-resistant human tumors by gene therapy.